“Do leaders change?”: A review of the contrasting behaviors of political leaders in ordinary-extraordinary situations - Arzu Özkanan; Yunus Yılan (Trakya Üniversitesi İktisadi ve İdari Bilimler Fakültesi E-Dergi)
The images of political leaders are affected by various factors such as their personality traits, leadership skills, behaviors, and attitudes. In times of crisis, the communication skills, leadership skills, and decision-making processes of political leaders are of great importance. The extraordinary situations brought about by the global pandemic constituted the focus of this study in order to determine and compare the behaviors of leaders in both ordinary and extraordinary conditions. In the study, the biographies, relevant scientific research, media, and official statements of the leaders of countries such as Germany, America, China, England, and Russia were transferred to the NVivo 10 program and examined, considering their pre-pandemic situations. The findings obtained reveal that the behaviors of leaders in ordinary and extraordinary situations vary. Angela Merkel moved away from stability during the period of uncertainty; Vladimir Putin maintained his authoritarian and oppressive leadership, but shifted from ideological leadership to pragmatic leadership. Boris Johnson, while defined as an ideological leader, has occasionally exhibited pragmatic behaviors. Donald Trump, on the other hand, adopted a pragmatic approach in ordinary times, but tried to strengthen this approach even further in extraordinary times.